2012
DOI: 10.1186/1476-4598-11-52
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of histone lysine demethylases in prostate cancer

Abstract: Early prostate cancer (PCa) is generally treatable and associated with good prognosis. After a variable time, PCa evolves into a highly metastatic and treatment-refractory disease: castration-resistant PCa (CRPC). Currently, few prognostic factors are available to predict the emergence of CRPC, and no curative option is available. Epigenetic gene regulation has been shown to trigger PCa metastasis and androgen-independence. Most epigenetic studies have focused on DNA and histone methyltransferases. While DNA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 71 publications
1
59
0
Order By: Relevance
“…www.impactjournals.com/oncotarget Metastasis suppressor genes (MSGs) are negative regulators of metastasis [10,11]. Compelling evidence indicates that modifications of DNA methylation and histones can silence the expression of MSGs, leading to the development of metastasis [12][13][14]. This notion is supported by studies of CRMP4, a novel prostate cancer MSG recently identified by our laboratory [15].…”
Section: Introductionsupporting
confidence: 51%
“…www.impactjournals.com/oncotarget Metastasis suppressor genes (MSGs) are negative regulators of metastasis [10,11]. Compelling evidence indicates that modifications of DNA methylation and histones can silence the expression of MSGs, leading to the development of metastasis [12][13][14]. This notion is supported by studies of CRMP4, a novel prostate cancer MSG recently identified by our laboratory [15].…”
Section: Introductionsupporting
confidence: 51%
“…As homeobox genes are master regulators, one possibility is that DNA methylation disturbs PRC-mediated regulation and may create a more stable silent state as opposed to a more dynamic state. Histone methylation, including H3K27me3, can be removed via well-known histone demethylases (47), whereas active DNA demethylation seems to be a more cumbersome process involving hydroxymethylation and DNA repair pathways (48,49). Another possibility is that genes with PRC marks in benign prostate cells are particularly susceptible to DNA methylation in prostate cancer, but that the latter is merely a by-product of overactive DNA methylation machinery.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the methylation level of lysine in histone is determined by the net activity of histone lysine methyltransferases and demethylases [43,60]. Dysfunction of these enzymes would give rise to abnormal histone methylation, possibly associated with disordered gene expression and even development of various diseases [59,61,62]. However, little effort has been made to elaborate a likely disturbance of histone methylation by nanomaterials.…”
Section: Discussionmentioning
confidence: 99%